Laser-ablation and induced nanoparticle synthesis. (March 2014) - Batani, Dimitri; Vinci, Tommaso; Bleiner, Davide
Abstract: Laser pulses are largely used for processing and analysis of materials and in particular for nano-particle synthesis. This paper addresses fundamentals of the generation of nano-materials following specific thermodynamic paths of the irradiated material. Computer simulations using the hydro code MULTI and the SESAME equation of state have been performed to follow the dynamics of a target initially heated by a short laser pulse over a distance comparable to the metal skin depth.